Analysis Stunting Prevention and Intervention: A Literatur Review - Marni Marni; Domingos Soares; Totok Wahyudi; Muhammad Irfan; Siti Nurul (Proceedings of the International Conference on Nursing and Health Sciences, 2022)
The incidence of stunting in Indonesia is still high, various efforts have been made by the government to reduce stunting. Stunting is a health problem that often occurs in children which can result in decreased productivity and intelligence in adulthood. This study aims to analyze the prevention factors for stunting at the age of toddlers. Checklist Prisma has been used for registration of titles, abstracts, full texts and methodologies with the keywords Analysis AND stunting AND Prevention AND Intervention. The computerized databases that have been used to search for articles in this study are Science Direct, Pubmed, ProQuest and Google Scholar. Has used articles that report quantitative and qualitative research in journals published in the period 2017 to 2022. The method used in data analysis is thematic analysis. This literature review involved 29 selected articles. There were 8 main factors that could affect stunting, namely nutrition/nutrition, economic status, education/knowledge, sanitation/environment, geographic location, government/cross-sectoral policies, age of marriage and health education. Most of the factors that contribute to stunting prevention are the provision of macronutrient/micronutrient supplements in the form of zinc tablets to adolescent girls, pregnant women, and supplementary feeding to children under five. Most of the studies reported in these 29 articles used a qualitative, quantitative design and were conducted in Bangladesh, China, India, Indonesia, Pakistan, Peru, Nepal, USA and Zimbabwe. In all these articles it is reported that the incidence of stunting is still high in several countries and especially in Indonesia. This literature review reported using 29 articles that met the inclusion criteria from the Science Direct, Pubmed, ProQuest and Google Scholar databases. The results detect the main factors that influence the occurrence of stunting, namely malnutrition in the early 1000 days of life, while for prevention is giving blood/zinc tablets to adolescents, pregnant women.